PRINSIP DAN APLIKASI DALAM MODIFIKASI SARANA DAN PRASARANA PENJAS - Saryono Saryono (Jurnal Pendidikan Jasmani Indonesia, 2008)
This paper describes the importance of modification equipment and facilities in physical education teaching learning for elementary level. One of the physical education qualities is indicated by the adequate equipment and facilities. The ratio of teachers, students, and the equipment and facilities is important data in preparing quality teaching physical education. Physical education in elementary level is the basic building of the national sport system. The adequate equipment and facilities will bring a foundation for children to enjoy physical activity in physical education programs. By including equipment and facilities for physical education and sport in the law such as National Sports System Acts No. 3, 2005 and Regulation of the Ministry of National Education No. 24, 2007 about equipment and facilities standards for schools, the government has clear authority and regulation. In fact, different school has different capacity to provide adequate equipment and facilities. This can be solved by modification of the games and sport either from number of players, and teaching strategies. It is also necessary that the modification of physical education equipment and facilities is appropriate for elementary students. Winning and losing in games which are part of physical education programs is not the main point but how the children play it. Kata Kunci : Modifikasi, sarana, prasarana, pendidikan jasmani